2014
DOI: 10.1371/journal.pone.0087626
|View full text |Cite
|
Sign up to set email alerts
|

Weak Power Frequency Magnetic Field Acting Similarly to EGF Stimulation, Induces Acute Activations of the EGFR Sensitive Actin Cytoskeleton Motility in Human Amniotic Cells

Abstract: In this article, we have examined the motility-related effects of weak power frequency magnetic fields (MFs) on the epidermal growth factor receptor (EGFR)-sensitive motility mechanism, including the F-actin cytoskeleton, growth of invasive protrusions and the levels of signal molecules in human amniotic epithelial (FL) cells. Without extracellular EGF stimulation, the field stimulated a large growth of new protrusions, especially filopodia and lamellipodia, an increased population of vinculin-associated focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 53 publications
4
21
0
Order By: Relevance
“…It has been shown that power frequency MF exposure acutely affects the migration/motility-related actin cytoskeleton reorganization in human amniotic epithelial cells 51 . It is proposed that power frequency MF-induced changes in the cytoskeleton are due to the presence of field-cell interaction sites at the plasma membrane level 51 52 53 , which may subsequently trigger a regulatory system that attempts to restore the HMF-disordered actin assembly. Therefore, the field-cell interaction is likely reduced by the HMF condition and would lead to a weakened restoration on the disordered actin assembly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that power frequency MF exposure acutely affects the migration/motility-related actin cytoskeleton reorganization in human amniotic epithelial cells 51 . It is proposed that power frequency MF-induced changes in the cytoskeleton are due to the presence of field-cell interaction sites at the plasma membrane level 51 52 53 , which may subsequently trigger a regulatory system that attempts to restore the HMF-disordered actin assembly. Therefore, the field-cell interaction is likely reduced by the HMF condition and would lead to a weakened restoration on the disordered actin assembly.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that a 30-min exposure of 0/1-0.5 mili Tesla (mT) power frequency magnetic field (MF) induced morphological and cytoskeletal changes in different cell lines [ 10 – 12 ]. In a way similar to EGF stimulation, a 30 min, 0.4 mT MF specifically upgraded cell migration, activated actin-cytoskeleton, induced a weakened F-actin network with denser filopodia and lamellipodia in leading edge, and re-distributed FA at cell level [ 13 ]. MF also induced responses at the protein level on signaling molecules such as F-actin nucleation protein Arp2/3, F-actin stabilizer protein fascin and MLC, as well as FA component vinculin etc .…”
Section: Introductionmentioning
confidence: 99%
“…We used the same system (I‐ONE, Shanghai, China) for magnetic field exposure of cerebellar GCs as has been used in previous studies, with some revisions . Briefly, a 50 Hz magnetic field was generated by a pair of horizontal Helmholtz coils (20 cm in height, and 20 cm in radius, each plate consists of 150 turns of copper wire) placed parallel to each other.…”
Section: Methodsmentioning
confidence: 99%